Socio-demographic Factors Associated with Stunting Among Children Under Five in Nigeria: Evidence from the 2024 Nigeria Demographic and Health Survey - Sri Nurcahyati; Widya Hary Cahyati; Eko Farida (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2026)
ntroduction: Nigeria continues to experience a substantial burden of stunting among children under five, with consequences that extend to long-term health outcomes, developmental capacity, and future productivity. The existence of these disparities underscores the need to further examine the association between social and demographic characteristics and the nutritional condition of children. Therefore, This study uses the most recent 2024 NDHS data to investigate the sociodemographic characteristics linked to stunting in Nigerian children under five. Methods: This study employed a quantitative cross-sectional methodology, utilizing secondary data from the 2024 Nigeria Demographic and Health Survey (NDHS), a national survey that was conducted in all 36 states and the Federal Capital Territory of Nigeria. The study analyzed 9,321 under-five children with complete anthropometric and socio-demographic information. Stunting, defined as a height-for-age z-score that is less than –2 standard deviations from the median reference in accordance with the WHO Child Growth Standards, was examined in relation to child, maternal, and household characteristics as independent variables. Using standardized DHS procedures, the study gathered data that were subsequently analyzed through weighted univariate and bivariate analyses, as well as multivariate binary logistic regression. Adjustments for clustering and stratification were performed with Taylor linearization, and statistical significance was defined as a p-value of less than 0.05. Results: The study found that 36.7% of children under five in Nigeria were stunted, with higher prevalence observed among older age groups, rural residents, children from low-educated and poorer households, and those in larger families. Bivariate analysis showed significant associations between stunting and children’s age, place of residence, birth weight, maternal education, religion, parity, maternal occupation, number of under-five children, and household wealth. Multivariable analysis identified that older age (36–47 months: AOR=4.01, 95% CI 3.20–5.01), rural residence (AOR=1.19, 95% CI 1.06–1.33), low birth weight (AOR=2.27, 95% CI 1.47–3.51), higher parity, and having more under-five children in the household were associated with significantly higher odds of stunting, while higher maternal education (AOR=0.55, 95% CI 0.43–0.70) and higher household wealth (richest vs poorest: AOR=0.29, 95% CI 0.23–0.36) were associated with lower odds of stunting. Religion was statistically associated with stunting after adjustment for the included covariates, though residual confounding from unmeasured geographic, ethnic, and structural factors cannot be excluded. Among all variables examined, current breastfeeding (DHS variable v404) was the only factor that showed no statistically significant association with stunting. Conclusion: Stunting among children under five in Nigeria is associated with child age, rural residence, low birth weight, maternal education, household socioeconomic status, parity, and the number of under-five children in the household, reflecting interconnected biological and socioeconomic associations. To address this issue, policy implications include targeted support for rural households, poorer households, mothers with low education, families with multiple under-five children, and children with low birth weight.